Impacts of COVID-19 on the mental health of health professionals: An integrative review - Dantas, Danilo Gonçalves; Silveira, Thatianna Souza da; Lima, Antonia Arlene; Sales, Andresa de Araújo; Haidar, Ana Leticia Ferreira; Oliveira, Marília Natache de; Rocha, Mariza Ozório da; Cunha, Denilson César Lopes; Ribeiro, Ítalo Arão Pereira; Fernandes, Márcia Astrês (Seven Editora, 2023)
Objective: To analyze the scientific evidence regarding the impacts of COVID-19 on the mental health of frontline healthcare workers. Methodology: integrative review study, which had as eligibility criteria: primary research, published between December / 2019 to October / 2020, without language restriction and that presented information on the subject. The research question was formulated following the assumptions of the acronym PICo, generating the question: What is the scientific evidence about the impacts on the mental health of health professionals who are on the front lines of the fight against COVID-19? The bibliographic survey took place in the following databases: MEDLINE via PubMed, CINAHL, EMBASE, SCOPUS, WOS, IBECS, LILACS, and BDENF via VHL. Results: 10 studies were analyzed, identifying the prevalence of studies published in the MEDLINE database, with the country of origin in China, cross-sectional studies, and having as participants doctors and nurses. The main impacts observed on the mental health of the professionals were: insomnia, depression, anxiety, fear, and stress, and these changes were more prevalent in females. Conclusion: the mental illness of health professionals during the pandemic reveals the need to strengthen strategies and actions that promote the mental health of these workers in the workplace, especially in periods such as these. DOI:https://doi.org/10.56238/emerrelcovid19-048